Phosphodiesterases 3 and 4 Differentially Regulate the Funny Current, I(f), in Mouse Sinoatrial Node Myocytes - St. Clair, Joshua R. (J Cardiovasc Dev Dis, 2017)
Cardiac pacemaking, at rest and during the sympathetic fight-or-flight response, depends on cAMP (3′,5′-cyclic adenosine monophosphate) signaling in sinoatrial node myocytes (SAMs). The cardiac “funny current” (I(f)) is among the cAMP-sensitive effectors that drive pacemaking in SAMs. I(f) is produced by hyperpolarization-activated, cyclic nucleotide-sensitive (HCN) channels. Voltage-dependent gating of HCN channels is potentiated by cAMP, which acts either by binding directly to the channels or by activating the cAMP-dependent protein kinase (PKA), which phosphorylates them. PKA activity is required for signaling between β adrenergic receptors (βARs) and HCN channels in SAMs but the mechanism that constrains cAMP signaling to a PKA-dependent pathway is unknown. Phosphodiesterases (PDEs) hydrolyze cAMP and form cAMP signaling domains in other types of cardiomyocytes. Here we examine the role of PDEs in regulation of I(f) in SAMs. I(f) was recorded in whole-cell voltage-clamp experiments from acutely-isolated mouse SAMs in the absence or presence of PDE and PKA inhibitors, and before and after βAR stimulation. General PDE inhibition caused a PKA-independent depolarizing shift in the midpoint activation voltage (V(1/2)) of I(f) at rest and removed the requirement for PKA in βAR-to-HCN signaling. PDE4 inhibition produced a similar PKA-independent depolarizing shift in the V(1/2) of I(f) at rest, but did not remove the requirement for PKA in βAR-to-HCN signaling. PDE3 inhibition produced PKA-dependent changes in I(f) both at rest and in response to βAR stimulation. Our results suggest that PDE3 and PDE4 isoforms create distinct cAMP signaling domains that differentially constrain access of cAMP to HCN channels and establish the requirement for PKA in signaling between βARs and HCN channels in SAMs.